Urban marketing for smart cities - Stefany CEVALLOS (Smart Cities and Regional Development Journal, 2022)
This article addresses the difference of Place, Image and Branding for urban marketing in Public Management of Ecuador. The government with the aim of planning and making decisions in real time should include the perspective of local governance and the construction of an image for its own country and the international arena to acelereate the local socio-economy development. This conceptual framework was designed to address the relationship between governance, and socio-economic development. The hypotheses proposed for this study were based on good governance and socio-economic development in Ecuador expected by the enforcement of urban marketing in Public Service Management moreover local governments are the key factors for translating investments revenues to sustainable economic development and, urban marketing as successful in terms of theory and practice when local governments are involved in the process as main actor to activate the economy of countries. The methodology used is secondary data sources including various types of books, journal articles, government reports and implementation plans.